Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Rumah Sakit Dr. Reksodiwiryo Padang - Finola, Finola; Yulasmi, Yulasmi; Bayu Pratama Azka (CV. ITTC INDONESIA, 2025)
The influence of reward and punishment on employee performance through work discipline as an intervening variable at dr. Hospital. Reksodiwiryo Padang City